The writing Caste – forms of contradiction in Faustina Bama’s Sangati - Rohrmoser, Gernot (Momentum Quarterly, 2020)
The present article sets out to examine Dalit feminist prose. Based on an analysis of Bamas Sangati, the attempt is made to elaborate the socio-critical and dalit-feminist aspects conveyed and encoded in the stories, dialogues and reflections. In addition, this discussion shows which concrete forms of contradiction the women portrayed develop. Contradiction manifests itself in questioning cultural and social norms, in striving for economic and social independence, in a positive transformation of discriminatory ascriptions of identity and at last in making visible an authentic (dalit-female) voice. Finally, it is demonstrated how the elaborated aspects could provide points of contact for political and social agitation in an extended social and scientific framework.
Keywords: Sangati; dalit-feminism; caste discrimination; strategies of emancipation